MUSICAL WORDS AND THEIR ROLE IN LEARNING FOREIGN LANGUAGES - Mohamed Ali Abdelwahed, (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
Teachers, especially foreign language instructors, need innovative methods to create an engaging and supportive learning environment. One approach is using musical words through poems, songs, and similar texts. This article explores their role and benefits in foreign language learning.